(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that modern conditions in the sports industry give rise to new directions of international cooperation in the field of physical culture and sports, which are defined as stable in time and space, complex in their organization, long-lasting, large-scale in terms of the number of participants, the territory of their implementation and coverage interested parties and united by subject and direction of complexes of international sports events, international sports competitions, services in the field of physical culture and sports, international sports competitions (Olympic, Paralympic, Deaflympic Games, etc.), as well as international projects in the field of physical culture and sports . Such areas of international cooperation in the field of physical culture and sports as international cooperation in martial law conditions, which include the implementation of international programs aimed at supporting athletes and their families, the introduction of scholarships for athletes who are forced to engage in sports in conditions with the support of leading international organizations, are highlighted martial law, international grants for the implementation of social projects aimed at ensuring a decent standard of living for athletes, full training in difficult security conditions; international cooperation in the field of business in the sports industry; international cooperation in the course of ensuring gender equality in the international space; development of cities and regions during international sports events; sports branding in the international context.